Berteologi Bersama Anak Jalanan: Kritik Ideologi Amos 5:1-17 dengan Perspektif Kaum Marginal - Ronaldo Sarimole; Juliana A Tuasela (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
The problem of street children is not only a condition that has only recently occurred but is a situation that has been going on for quite a long time, even since the Bible was written. Children are used as property for economic and socio-political purposes. Even children who do not make a good contribution to the family are often subjected to immoral actions, such as being thrown onto the street, sold as slaves to pay off family debts, or even killed. One of the Bible texts, especially the Old Testament (PL), that shows this reality is the text Amos 5:1–17 because it contains the injustice experienced by marginalized people, especially street children. This article aims to carry out an interpretation using ideology, criticism, and the perspective of marginalized people. The findings highlight the issue of child injustice and offer a pro-life viewpoint that honors the worth of children. The findings are discussed starting from conducting ideological criticism of Amos's text, exposing the reality of street children, to showing prophetic criticism that provides new energy in overcoming social problems from the reality of street children.